Report from the COVID-19 Virtual Summit, Disaster Experts Speak Out, March 31, 2020. Issue 4 (21st August 2020) - Phillips, James P.; Ragazzoni, Luca; Burel, W. Greg; Burkle, Frederick M.; Keim, Mark
Abstract: This article captures the webinar narrative on March 31, 2020 of four expert panelists addressing three questions on the current coronavirus disease 2019 (COVID-19) pandemic. Each panelist was selected for their unique personal expertise, ranging from front-line emergency physicians from multiple countries, an international media personality, former director of the US Strategic National Stockpile, and one of the foremost international experts in disaster medicine and public policy. The forum was moderated by one of the most widely recognized disaster medical experts in the world. The four panelists were asked three questions regarding the current pandemic as follows: 1. What do you see as a particular issue of concern during the current pandemic? 2. What do you see as a particular strength during the current pandemic? 3. If you could change one thing about the way that the pandemic response is occurring, what would you change?